11(8r+3)2(9-6r)=

Simple and best practice solution for 11(8r+3)2(9-6r)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 11(8r+3)2(9-6r)= equation:


Simplifying
11(8r + 3) * 2(9 + -6r) = 0

Reorder the terms:
11(3 + 8r) * 2(9 + -6r) = 0

Reorder the terms for easier multiplication:
11 * 2(3 + 8r)(9 + -6r) = 0

Multiply 11 * 2
22(3 + 8r)(9 + -6r) = 0

Multiply (3 + 8r) * (9 + -6r)
22(3(9 + -6r) + 8r * (9 + -6r)) = 0
22((9 * 3 + -6r * 3) + 8r * (9 + -6r)) = 0
22((27 + -18r) + 8r * (9 + -6r)) = 0
22(27 + -18r + (9 * 8r + -6r * 8r)) = 0
22(27 + -18r + (72r + -48r2)) = 0

Combine like terms: -18r + 72r = 54r
22(27 + 54r + -48r2) = 0
(27 * 22 + 54r * 22 + -48r2 * 22) = 0
(594 + 1188r + -1056r2) = 0

Solving
594 + 1188r + -1056r2 = 0

Solving for variable 'r'.

Factor out the Greatest Common Factor (GCF), '66'.
66(9 + 18r + -16r2) = 0

Factor a trinomial.
66((3 + -2r)(3 + 8r)) = 0

Ignore the factor 66.

Subproblem 1

Set the factor '(3 + -2r)' equal to zero and attempt to solve: Simplifying 3 + -2r = 0 Solving 3 + -2r = 0 Move all terms containing r to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -2r = 0 + -3 Combine like terms: 3 + -3 = 0 0 + -2r = 0 + -3 -2r = 0 + -3 Combine like terms: 0 + -3 = -3 -2r = -3 Divide each side by '-2'. r = 1.5 Simplifying r = 1.5

Subproblem 2

Set the factor '(3 + 8r)' equal to zero and attempt to solve: Simplifying 3 + 8r = 0 Solving 3 + 8r = 0 Move all terms containing r to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + 8r = 0 + -3 Combine like terms: 3 + -3 = 0 0 + 8r = 0 + -3 8r = 0 + -3 Combine like terms: 0 + -3 = -3 8r = -3 Divide each side by '8'. r = -0.375 Simplifying r = -0.375

Solution

r = {1.5, -0.375}

See similar equations:

| 16n^2-161n=-5n^2-280 | | 9x^2-12x-8=0 | | -5x-30=3(x+4) | | 2y+2=9 | | X^2=2x+5 | | 675=4.50x | | 514=81.4+x | | (x-1)^2/3=4 | | 20x^3+60x^2+40= | | -10n+3(8+8n)=-6(x-4) | | 15/tan27 | | 4-7+3s-5s+1= | | y=-0.6x+1 | | 4-4=8s-2s | | 3x-25=2 | | x^2-3x-29=0 | | x=2/x | | x^2-2x-31=0 | | 12t-50=4t+14 | | 10(x-4)-2x=4x+2(2x+10)+20 | | 3y=y+48 | | -8x-3x-4x= | | (4/3)3.14(16•16•16) | | n/5=76 | | -1/9g=-12 | | 6x-8+3x-10=360 | | p+16=3 | | -sqrt(36-9x)+4=x | | u^2+7u-18=0 | | 30x^3-55x^2y^2-50xy^3= | | x-5=2-(x+1) | | (2x+15)+7x+2x=180 |

Equations solver categories